Language Learning Strategies of Non-Muslim Students Applied to Arabic Language Course Inside and Outside the Classroom - Arifin, Zamri; Abu Bakar, Nur Khadijah; Ridzwan, Zaharom; Jamsari, Ezad Azraai (Ijaz Arabi Journal of Arabic Learning, 2021)
Students of foreign language require prior exposure to language learning strategy so that each of them positively perceives the target language. Thus, this research is conducted to identify the Arabic language learning strategy used by non-Muslim students in and outside the classroom. Research respondents comprise 37 non-Muslim students of the Law Faculty of Universiti Kebangsaan Malaysia (UKM). Arabic language course SKVA2552 Preparatory Arabic Course for the Law Faculty is compulsory for all non-Muslim students in the first semester of the Bachelor of Law program at the Law Faculty in UKM. This research uses a questionnaire instrument based on the model theory of language learning strategy by Embi (2000). Research shows that all non-Muslim students who take the course do not know the basics of Arabic language and comprise of diverse races and ethnicity. Non-Muslim students prefer to use the learning strategy while in the classroom learning process rather than outside the classroom, with the highest mean value and standard deviation (mean=3.24; p=0.863) for item B7 ‘I request my friends to re-explain if I don’t understand the teacher’s explanation on the Arabic language’. Therefore, this research basically evaluates the teaching and learning process (TL) of Arabic language among non-Muslim students to make it more approachable. The research implies that the basic Arabic language module can be purified to be simpler based on the target scope of non-Muslim students to improve Arabic language achievement for adjusting the course to be compulsory at the level of the entire university.